Larval development of Cyrtograpsus affinis (Dana) (Decapoda, Brachyura, Varunidae) from Río de la Plata estuary, reared in the laboratory - Eduardo D. Spivak; José A. Cuesta (Scientia Marina, 2000)
The complete larval development of the crab Cyrtograpsus affinis (Brachyura, Varunidae) was obtained by culture in the laboratory. Five zoeal stages, the megalopa and the first crab are described and illustrated. Larval development from hatching to first crab took 29 days at 20° C and 35 PSU. The genus Cyrtograpsus only consists of three species. Larval development of C. altimanus and C. angulatus had been described previously. In the present study, morphological larval characters of the three species are compared. Generic larval features are also compared with those of other Varunidae genera.